Гігієнічна оцінка біологічної контамінації поверхневих водойм Українського Придунав’я = Hygienic assessment of Ukrainian Danube region surface water bodies biological contamination - Kovalchuk, L. I.; Korobchansky, V. A.; Mokienko, A. V. (Journal of Education, Health and Sport, 2015)
Kovalchuk L. I., Korobchansky V. A., Mokienko A. V. Гігієнічна оцінка біологічної контамінації поверхневих водойм Українського Придунав’я = Hygienic assessment of Ukrainian Danube region surface water bodies biological contamination. Journal of Education, Health and Sport. 2015;5(7):533-541. ISSN 2391-8306. DOI 10.5281/zenodo.28043 http://dx.doi.org/10.5281/zenodo.28043 https://pbn.nauka.gov.pl/works/607551 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A533-541 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. УДК 613.32:614.445(477.74) Гігієнічна оцінка біологічної контамінації поверхневих водойм Українського Придунав’я Hygienic assessment of Ukrainian Danube region surface water bodies biological contamination * Л. Й. Ковальчук, ** В. О. Коробчанський, *** А. В. Мокієнко * L. I. Kovalchuk, ** V. A. Korobchansky, *** A. V. Mokienko *Одеський національний медичний університет; **Харківський національний медичний університет; *** Державне підприємство Український науково-дослідний інститут медицини транспорту Міністерства охорони здоров’я України, м. Одеса *Odessa National Medical University; **Kharkiv National Medical University; ***State Enterprise Ukrainian Research Institute for Medicine of Transport of the Ministry of Health Care of Ukraine, Odessa Abstract The objective: to conduct hygienic assessment of Ukrainian Danube region surface water bodies biological contamination. Definite levels of biological contamination has been indicated which points to low efficiency of wastewater treatment. The predominant viral contaminants rotaviruses and adenoviruses which is consistent with the data of literature. The percentage of water contamination by oocysts Cryptosporidium spp. is rather high and equals to 60%. This indicates the presence of persistent sources of anthropogenic pollution. Epidemiological adversity of the region under study due to anthropogenic pollution of water reservoirs by opportunistic and pathogenic microflora has been justified. These conditions are favorable for breeding of V. cholerae, Legionella, leptospirosis and tularemia pathogens. Possible negative impact of cyanotoxins on human health as a result of mass multiplication of cyanobacteria, especially Aphanizomenon flos-aquae, Synechocystis salina, Spirulina laxissima, Merismopedia minima, which cause "flowering" of water in the lakes Cahul, Yalpug, Katlabuh has been proved. The necessity of introduction of more efficient, compared to chlorine disinfection of water resources and systematic microbiological, virological, parasitological and algological water monitoring of water using modern research methods has been substantuated. Keywords: water, surface water, biological contamination, Ukrainian Danube region. Реферат Мета роботи полягала у гігієнічній оцінці біологічної контамінації поверхневих водойм Українського Придунав’я. Встановлені певні рівні біологічної контамінації, що свідчить про низьку ефективність очищення стічних вод. Переважаючими вірусними контамінантами водних об’єктів є АВ та РВ, що узгоджується з даними літератури. Показано високий відсоток (60 %) контамінації води ооцистами Cryptosporidium spp., що свідчить про наявність персистувальних джерел антропогенного забруднення. Обгрунтовано епіднеблагополуччя регіону Українського Придунав’я у зв’язку із антропогенним характером забруднення води досліджених водойм умовно-патогенною та патогенною мікрофлорою та сприятливістю для розмноження холерних вібріонів, легіонел, збудників туляремії та лептоспірозу. Висловлено думку щодо можливого негативного впливу ціанотоксинів на здоров’я населення внаслідок масового розмноження ціанобактерій, зокрема Aphanizomenon flos-aquae, Synechocystis salina, Spirulina laxissima, Merismopedia minima, які викликають «цвітіння» води, в озерах Кагул, Ялпуг, Катлабух. Обгрунтовано необхідність впровадження більш ефективних, у порівнянні із хлором, засобів знезараження води та проведення систематичного мікробіологічного, вірусологічного, паразитологічного та альгологічного моніторингу води поверхневих водойм Українського Придунав’я із застосуванням сучасних методів досліджень. Ключові слова: вода, поверхневі водойми, біологічна контамінація, Українське Придунав’я. Реферат ГИГИЕНИЧескАЯ ОЦЕНКА БИОЛОГИЧЕСКОЙ КОНТАМИНАЦИИ поверхностных водоемов УКРАИНСКОГО ПРИДУНАВьЯ. Цель работы состояла в гигиенической оценке биологической контаминации поверхностных водоемов Украинского Придунавья. Установлены определенные уровни биологической контаминации, что свидетельствует о низкой эффективности очистки сточных вод. Преобладающими вирусными контаминантами воды являются аденовирусы и ротавирусы, что согласуется с данными литературы. Показан высокий процент (60 %) контаминации воды ооцистами Cryptosporidium spp., что свидетельствует о наличии персистирующих источников антропогенного загрязнения. Обосновано эпиднеблагополучие региона Украинского Придунавья в связи с антропогенным характером загрязнения воды исследованных водоемов условно-патогенной и патогенной микрофлорой и благоприятностью для размножения холерных вибрионов, легионелл, возбудителей туляремии и лептоспироза. Высказана мысль относительно возможного негативного влияния цианотоксинов на здоровье населения вследствие массового размножения цианобактерий, в частности Aphanizomenon flos-aquae, Synechocystis salina, Spirulina laxissima, Merismopedia minima, которые вызывают «цветение» воды, в озерах Кагул, Ялпуг, Катлабух. Обоснованы необходимость внедрения более эффективных, по сравнению с хлором, средств обеззараживания воды и проведение систематического микробиологического, вирусологического, паразитологического и альгологического мониторинга воды поверхностных водоемов Украинского Придунавья с применением современных методов исследований. Ключевые слова: вода, поверхностные водоемы, биологическая контаминация, Украинское Придунавье.